Áp dụng công nghệ điện toán đám mây trong các cơ quan thông tin-thư viện Việt Nam và kết quả thử nghiệm tại Cục Thông tin khoa học và công nghệ quốc gia - Phan, Huy Quế (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Introducing the definition, implementation and related services of cloud computing. Analyzing its benefits for information centers and libraries. Introducing the catalyst position of information centers and libraries when applying cloud computing and the experimental results of applying cloud computing at the National Agency for Science and Technology Information's VinaREN center.